Peasants under Siege : The Collectivization of Romanian Agriculture, 1949-1962 - Kligman, Gail; Verdery, Katherine, 1948- (Book collections on Project MUSE., 2011)
In 1949, Romania's fledgling communist regime unleashed a radical and brutal campaign to collectivize agriculture in this largely agrarian country, following the Soviet model. Peasants under Siege provides the first comprehensive look at the far-reaching social engineering process that ensued. Gail Kligman and Katherine Verdery examine how collectivization assaulted the very foundations of rural life, transforming village communities that were organized around kinship and status hierarchies into segments of large bureaucratic organizations, forged by the language of "class warfare" yet saturat